Pemanfaatan Accelerometer Pada Telepon Genggam Berbasis Android Sebagai Kendali Mobile Robot - Surjoputro, Christoforus; Harianto, Harianto; Puspasari, Ira (Journal JCONES, 2012)
During this time, used of accelerometer sensor is very helpful in human life, generally in automotive needed.Use of this sensor as a detector for airbag in car is worthy to be removed or not in cars accident event. The other used of this sensor is to see the movement of aircraft from its starting point. The conclution of the used of accelerometer sensor in automotive field wal limited to making a decision and see the movement of object. In mobile phone technology, this sensor is able to used as an interaction between user and applications. Generally for game application. There are several games that used this sensor to perform some actions. It can also be seen that the utilization in mobile phone technology was limited to the interaction of an application. From both limitation, the authors attempt to use the sensor in other field with other uses. This time, the sensor is used to control a mobile robot from the axis change that are detected by sensor on mobile phone. Users are expected to get more experience in utilization of this sensor, the user can control the mobile robot as playing games in mobile phone. This application are meneged to control the mobile robot based on the axis change that occur in mobile phone. Beside that, this application also managed to show images that captured from mobile robot so the user can control the mobile robot although the robot can´t be seen. There is a problem that the mobile phone has a long respon to show an image on the display and it disturb the user. Keyword: Mobile Robot, Robotino, Telepon Genggam, Android, accelerometer.